Effect of GnRH analogues upon height in girls with a late diagnosis of central precocious puberty - Martínez, Melissa (2020)
Objective: to assess the effect of GnRH analogues on predicted adult final height in girls with a late diagnosis of central precocious puberty. Material and methods: this is a descriptive and retrospective study. Girls seen between 2012 and 2018 in the Pediatric Endocrinology Unit of Hospital Nacional Cayetano Heredia with a late diagnosis of idiopathic precocious central puberty were included. Anthropometric assessments were performed, Tanner stage assessment and bone age determination using the Greulich and Pyle method were performed, and the final adult height was predicted using the Bailey Pinneau method before and after therapy. A Student-t test was used for comparing the height prediction before and after therapy. A p<0.05 value was considered as significant. Results: twenty-three girls with mean chronological age 8.4 ± 0.4 years were included. Their bone age was 10.7 ± 0.8 on admission. Most of the patients (83.9%) were overweight and 74.3% were Tanner 3 at the time of diagnosis. The average time using GnRH analogues therapy was 20.5 ± 8.4 months. The effect of therapy, which was calculated using the prediction difference for the final adult height minus the initial height prediction was 2.5 ± 4.1 cm (p<0.001). Conclusion: girls with a diagnosis of late diagnosis central precocious puberty show a discrete benefit on the prediction of the final adult height, so therapy at this age should be individualized.